Degradasi Methylene Blue Melalui Metode Fotokatalitik Menggunakan Covalent Triazine Framework-Copper (CTF-Cu) Sebagai Fotokatalis - Siregar, Ricky Putra; Saputra, Edy; Utama, Panca Setia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Textile industries in Indonesia have been growing year by year and have an important role in economic system. However, their enhancement raises environmental pollution because of their dye wastes. Either small-scale or large-scale contamination have massively spoiled some rivers in Indonesia, such as Ciliwung, Cisadane, and Bengawan Solo. Therefore, a special method like photocatalytic is highly needed to handle it. Photocatalytic method is able to degrade dyes quickly by producing hydroxyl radical (•OH) as a strong oxidant. One of the best photocatalysts to use is covalent triazine framework (CTF) with copper (Cu) as catalyst doping synthesized by using an ionothermal method. Photocatalytic degradation of methylene blue reached the highest degradation performance 95,02%. Keywords: textile, photocatalytic, hydroxyl radical, covalent triazine framework, ionothermal